The Children & Young People (Scotland) Act 2014: implications for residential care - Iain Macauley (Scottish Journal of Residential Child Care)
The Children and Young People (Scotland) Act 2014 contains several changes to how children and young people in Scotland will receive services. This has particular relevance for residential care and this paper will explore some of the issues for residential child care arising from the Act and its implementation. In this article the Act will be considered as a driver for residential childcare developing a focus beyond the residential service.